2014
DOI: 10.1080/01457632.2014.916162
|View full text |Cite
|
Sign up to set email alerts
|

Study on SO2-Absorption Behavior of Composite Materials for DeSOxFilter From Diesel Exhaust

Abstract: 4DENOSO Corporation, Kariya city, Aichi Prefecture, Japan NO x emitted from diesel engines is one of the major air pollutants in most countries. To reduce NO x emission, NO x storage/reduction (NSR) catalysts have been developed for diesel systems. The catalyst for NSR is strongly poisoned with sulfur. This paper reports the synthesis of Na-doped CaCO 3 as a new material for SO 2 adsorption. Measurements of the desulfurization breakthrough characteristics using monolith washcoated Na-doped CaCO 3 were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The low-temperature sulfate activation of the alkali metals doped MnO 2 depends on the oxidation of SO 2 [11]. The sulfate reactivity of the oxygen species was investigated by means of H 2 -TPR analysis.…”
Section: Mechanism For the Improvement Of Low-temperature Desulfurizamentioning
confidence: 99%
See 1 more Smart Citation
“…The low-temperature sulfate activation of the alkali metals doped MnO 2 depends on the oxidation of SO 2 [11]. The sulfate reactivity of the oxygen species was investigated by means of H 2 -TPR analysis.…”
Section: Mechanism For the Improvement Of Low-temperature Desulfurizamentioning
confidence: 99%
“…It is found that the formed K 2 SO 4 was quite stable in the range between 180 °C and 550 °C. Osaka et al described the synthesis of Na‐doped CaCO 3 as a new material for SO 2 adsorption, and the sulfur absorption capacity of Na‐doped CaCO 3 was improved compared with fresh CaCO 3 . These studies discussed only the effects of SO x sorption of the potassium or sodium‐based sorbents; however, the SO 2 removal performance of lithium‐based MnO 2 sorbents is not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that alkali metal oxides and alkaline-earth metal oxides present in coal fly ash partially capture acidic gaseous sulfur oxides, which are present in the flue gas [7,13,14]. However, to achieve sufficient solidification, alkaline sorbents are additionally being sprayed into the furnace or into the flue gas, such as CaO, MgO, Na 2 CO 3 , Ca (OH) 2 and Mg(OH) 2 [15][16][17][18][19][20][21]. Among the sorbents mentioned above, calcium-based sorbents are the most commonly used because they are affordable, easy to obtain and can remove SO 3 with a high efficiency (above 80%) [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the amorphous citric acid complex method is focused on as a physically modification of CaCO 3 [4]. Then, base adducted complex method is focused on the chemically modification of CaCO 3 [5]. CaCO 3 having more low temperature activation is proposed by combining both method.…”
Section: Introductionmentioning
confidence: 99%